Exploring the multitude of risk factors associated with early childhood caries - Madhu Kakanur; Mihir Nayak; Sandyadevi S Patil; Rachna Thakur; Santhosh T Paul; Nisha Tewathia (Wolters Kluwer Medknow Publications, 2017)
Context: Despite efforts in restorative therapy, children who experience Early Childhood Caries (ECC) continue to be at a higher risk for new lesions in both the primary and the permanent dentition. Early interventions which disrupt the pathobiology of caries need identification of all the causative or risk factors. Aims and Objectives: This study dealt with the prevalence and associated risk factors of ECC among preschool children aged 3 to 5 years in Bengaluru city. Materials and Methods: Information regarding risk factors was obtained through a structured questionnaire among a random sample of 1152 children. Clinical examination was performed by a trained dental professional using the modified WHO oral health survey format. Statistical Analysis: Chi-square, one-way ANOVA, correlation, multiple linear regression analysis. Results: The prevalence of ECC among preschool children was 24.39% (P < 0.05), whereas the mean deft was 5.80 ± 8.90. The prevalence of ECC among males and females was 24.92% and 23.81%, respectively. 4.27% of children with ECC showed a history of prolonged breastfeeding beyond 2.5 years (P < 0.05). 50.18% of children had a history of using medications during bedtime/night. History of low birth weight was reported among 23.84% of ECC children. Only 13.52% of mothers claimed of getting a prenatal oral health care/counseling (P < 0.05). Conclusion: The prevalence of ECC was seen in almost a quarter of the population with a high deft. A significant relation was associated only with the feeding duration and lack of prenatal oral health counseling provided to parents.